'The sun is far away, but there must be the sun': Chinese students' experiences of an international teaching practicum in China. Issue 4 (1st October 2020) - Jin, Aijing; Parr, Graham; Hui, Leng
ABSTRACT: Background: Small cohorts of pre-service teachers (PSTs) have been successfully undertaking teaching practicums in a range of international settings for more than 40 years, as part of their initial teacher education studies. Most research into these international teaching practicums (ITPs) has concentrated on the benefits for western PSTs and their western academic mentors, but limited attention has been paid to the experiences, benefits and challenges of non-western practicum partners. The study addresses this gap in the literature by focusing on Chinese students' perceptions of a three-week international teaching practicum in China. Purpose: The purpose of the study was to examine the experiences of Chinese students who were taught by Australian PSTs as part of an international teaching practicum in China. Method: Using content analysis methods and a border-crossing theoretical framework, this small scale qualitative case study analysed, in depth, the reflective writing of Year 7 (12- to 13-year-old) and Year 11 (16- to 17-year-old) students from three schools across two different cities in China. Findings: The analysis indicated that students enjoyed the practicum experience, with many of the older students showing a nuanced appreciation of the cultural and pedagogical contrasts between the Australian PSTs' teaching of English and that of their usual Chinese teachers. While some students were concerned that the Australians' teaching did not adequately prepare them for high-stakes national tests, others reported that their whole attitude to learning English had changed so that English was now one of their favourite subjects as a result of being taught by the Australian pre-service teachers. Conclusions: Through investigating local Chinese students' experiences of an international teaching practicum, this study contributes to the now substantial body of literature that affirms the value of such intercultural education programmes. The study argues for the value of intercultural 'crossing over' experiences for non-western as well as western practicum partners, and urges educational researchers to listen to the voices of local students when researching international teaching practicums.